Development of an Integrated On‐Line 2D Analytical TREF‐High Throughput SEC Technique for Polyolefins Characterization. Issue 1 (27th April 2020) - Yu, Youlu; Hildebrand, Melvin
Abstract: Complete polymer compositional information of polyolefins is critically valuable in understanding the polymer structure‐processing‐property relationship, thus helping tailor‐design polymers with desired end‐use properties. In this paper, a robust on‐line 2D analytical TREF combined with high‐throughput SEC technique (2D aTREF‐hSEC) is described that can rapidly determine the bivariate distribution of chemical composition and molecular weight of polyethylene resins. Unlike Nakano and Goto's pioneering cross fractionation apparatus and the commercial CFC instrument, this 2D aTREF‐hSEC system has the following unique characteristics: First of all, the GPC injection volume is not limited by the dead volume of the full TREF column. It can be set at any desired values to ensure optimized separation in SEC. Second, the flow rates for the TREF and SEC unit are independently controlled, which add operational flexibility and help optimize the separation efficiency in both the TREF and the SEC dimension. Third, the 2D aTREF‐hSEC system runs continuously instead of stepwise. Once started, the TREF column elutes continuously without stopping to wait for the completion of downstream SEC elution before the next SEC injection, increasing the resolution in TREF dimension. Fourth, experimental time is significantly reduced thanks to the employment of high throughput SEC column. And finally, this 2D aTREF‐hSEC technique in principle can be applied equally well to characterize other semi‐crystalline polymers and potentially any polymers whose solubility is a function of temperature.